Effects of negative life events on depression in middle school students: The chain-mediating roles of rumination and perceived social support - Xia, Hui; Han, Xuexue; Cheng, Jing; Liu, Debiao; Wu, Yili; Liu, Yan (Frontiers in Psychology, 2022)
Background Negative life events in middle school students have a significant impact on depression. However, the mechanism of this association is not fully understood. This study used rumination and perceived social support as mediating variables to explore the influence of life events on depression. Methods Due to the COVID-19 pandemic and social distancing, a convenient sampling method was adopted to collect information about middle school students in Shandong Province by means of online questionnaire. Adolescent Self-Rating Life Events Check List, Ruminative Responses Scale, Perceived Social Support Scale and Children’s Depression Inventory were used. Descriptive statistics and correlation analysis were conducted for four variables of middle school students, including life events, depression, rumination thinking and perceived social support, and the chain mediated effect was tested by using process plug-in. All statistically analysis was conducted by SPSS 23.0. Results 493 middle school students (16.70±0.95 years) including 343 female students (69.60%) from Shandong Province recruited. Results showed that the total effect between life events and depression was significant (effect=0.2535, 95%CI: 0.2146,0.2924). The total indirect effect was significant (effect=0.1700, 95%CI:0.1349,0.2072). The indirect effect was significant (effect=0.0988, 95%CI: 0.0741,0.1252) with rumination as the mediating variable. The indirect effect of pathway with perceived social support as the mediating variable was significant (effect=0.0476, 95%CI: 0.0295,0.0674). The indirect effect of pathway with rumination and perceived social support as mediating variables was also significant (effect=0.0236, 95%CI: 0.0147,0.0339). Conclusions This study indicated that ruminant thinking and perceived social support had a significant chain mediating effect on adolescents' life events and depression. Life events can not only directly affect depressive emotions, but also indirectly affect depressive emotions by affecting ruminant thinking and perceived social support. The results of this study not only provide new directions for the relationship between life events and depression, but also provide possible approaches for future prevention and intervention of depression in middle school students. Keywords Middle school student; Negative life events; Depression; Rumination; Perceived social support; Chain mediation